Soccer: Basic Principles of What to Teach, and Why
This section is about the basic principles of what you should try to teach your players, and what those things are important. The actual mechanics of the coaching sections can be found in the "Teaching the Basics" section. Here's what you'll find here: 1.Expectations after one year 2.The Most Important Skills to Teach 3.Formations and positional skills 4.Individual Attacking 5.Group Attacking 6.Individual Defending 7.Group Defending